Representation of Minangkabau Women in the Formation of Digital Culture (A Critical Ethnographic Study of the Entrepreneurship Sector) - Reni Novia; Rizki Briandana; Heri Budiyanto (Social and Economic Bulletin, 2026)
Title: Representation of Minangkabau Women in the formation of digital Culture : A Critical Etnographic Study Of the entreupreunership. Purpose: This study aims to explore the transformation and representation of Minangkabau cultural identity within the framework of the digital economy. Specifically, this research formulates the study on how Minangkabau women entrepreneurs, who are traditionally rooted in a matrilineal system, negotiate cultural values when engaging in modern digital business practices.Methodology: This study uses a Systematic Literature Review (SLR) with the PRISMA approach. Data was synthesized from 30 high-quality articles (2016-2026) indexed in Scopus, SINTA, and Google Scholar, focusing on the intersection of matrilineality, gender roles, and digital entrepreneurship.Results: Data synthesis reveals three main "new cultural representations": (1) Deconstructing the concept of "Merantau" into "Digital Merantau," where geographical boundaries are broken thru virtual migration; (2) The evolution of Bundo Kanduang into a "Digital Manager" who uses hybrid branding by combining the values of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) with modern digital esthetics; and (3) The emergence of "Digital Double Burden," where technological agency coexists with traditional domestic expectations.Implication: This research contributes to the socio-economic literature by presenting a framework on deep modernity, describing how the digital economy does not erode the values of local wisdom in matrilineal societies, but rather provides a new platform for their revitalization and expansion.